2014
DOI: 10.1037/fsh0000002
|View full text |Cite
|
Sign up to set email alerts
|

Associations between relationship status and day-to-day health behaviors and weight among diverse young adults.

Abstract: Introduction Previous research has shown strong positive associations between physical and psychological health outcomes and being in a committed relationship, such as marriage, however little research has investigated whether being in a committed relationship is protective for day-to-day health behaviors such as dietary patterns and physical activity. The main aim of this paper is to examine associations between relationship status and day-to-day health behaviors (e.g. dietary intake, physical activity) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
2
6
0
2
Order By: Relevance
“…This nding is somewhat in line with many studies that report positive contribution of marriage to body weight, where the gain is greater for males (e.g. Sobal et al 2003;Berge et al, 2014;Teachman, 2016). 9 Farrell and Shields (2002)'s calculation of intra-household correlation in sport participation based on British data is 0.357.…”
Section: Sedentarinesssupporting
confidence: 85%
“…This nding is somewhat in line with many studies that report positive contribution of marriage to body weight, where the gain is greater for males (e.g. Sobal et al 2003;Berge et al, 2014;Teachman, 2016). 9 Farrell and Shields (2002)'s calculation of intra-household correlation in sport participation based on British data is 0.357.…”
Section: Sedentarinesssupporting
confidence: 85%
“…Previous research showing associations of diet with the home environment [ 12 15 ], employment status [ 16 ] and relationship status [ 17 , 18 ] have primarily been cross-sectional. For example, cross-sectional studies have demonstrated associations between adolescent diet quality and factors related to the family home environment, such as associations between availability of particular foods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining associations between relationship status and health behaviours have shown mixed results. A cross-sectional study from the US found no associations between relationship status and fruit and vegetable, sugar-sweetened beverages (SSB) or fast food intake frequency among young adults [ 17 ], while a longitudinal study of young Australians found no differences in change in diet quality between those who began partnership relationships and those who did not [ 25 ]. Meanwhile in a Swiss adult sample, associations were seen between cohabitation and higher vegetable intake particularly among males [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, evidence on the influence of relationship status on physical activity and body weight has been inconsistent [ 17 ]. Some studies [ 18 20 ] have shown higher rates of physical inactivity and overweight in couples, while other studies [ 8 , 21 , 22 ] have reported higher rates in singles, or no association with relationship status [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%